Theoretical investigation of coupling between a laser diode and a lensed fiber - FAIDZ, A; MISHRA, V (2003)
In this paper, we present a simple analysis, utilising the ABCD transformation matrix method, to analyze and determine the coupling efficiency between a laser diode and a conically lensed fiber. The calculated and measured results, i.e. the coupling efficiencies, were compared for microlenses etched at 20, 30 and 40 minutes. We found that the calculated results were in good agreement with the measured values.